EXPORTS AND ECONOMIC GROWTH; A Comparison between Indonesia and Singapore - Yudo Swasono; Endang Sulistyaningsih (Journal of Indonesian Economy and Business (JIEB), 1989)
Much empirical evidence suggest that countries with high growth export ratestend to enjoy a high economic growth. Increasing the volume of exports directlyincreases national income through a national income equation. A recent theorysuggests that exports increase national income indirectly through spill over effectsthat improve income and reduction costs.  This paper attempts to investigate the role of exports in explaining the growth of the economy, both directly and indirectly, in two countries Singapore and Indonesia, following the economics model developed by Feder, 1982, based on the framework anlysis developed by previous authors in these fields (Michalopoulos and Jay, 1973 and Balasa, 1978). The paper starts by presenting a short description of the economic background of Indonesia and Singapore (in section 2). Section 3 discusses the anlytical framework and economerics models used in this investigation, and section 4 presents the empirical analysis and comparison of the results in this two cases.